The Use of Quantum Learning Model with Islamic Character Values to Improve Fifth Graders’ Academic Achievement - Muhamad Afandi; Sri Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2020)
This study aims at describing the use of quantum learning model with Islamic character values to improve students’ achievement at elementary school. It used a descriptive qualitative method. Data were collected through observation, in-depth interview and documentation. The result indicates that quantum learning model with Islamic character values is beneficial for students during the teaching and learning process. These cover students feel more active in the learning process, students have more attention on teachers’ explanations, students have better academic achievement which is shown by the average score among students passing the minimal criteria standard and learning processes and students are able to internalize the Islamic values during teaching and learning process.